Effects of practice schedules on speech motor learning. (October 2013) - Wong, Andus W.-K.; Whitehill, Tara L.; Ma, Estella P.-M.; Masters, Rich
Abstract: The aim of this study was to evaluate the effects of various practice schedules on learning a novel speech task. Forty healthy Cantonese speakers were asked to learn to produce a Cantonese phrase with two target utterance durations (2500 and 3500 milliseconds). They were randomly assigned to one of four learning conditions, each completing a different practice schedule, namely Blocked only, Random only, Blocked-then-Random, and Random-then-Blocked. Two retention tests (one immediate and one delayed) and a transfer test were administered. The four groups of participants showed different patterns of learning, but achieved comparable levels of performance at the end of the acquisition phase. However, participants in the Blocked only condition were less able to differentiate the two target durations than those in the Random only condition during retention. Furthermore, participants who received both blocked and random practice were less adversely affected by the secondary task during the transfer test than those who received either blocked or random practice alone. These findings suggest that mixed practice schedules are more effective than either blocked or random practice, especially in transferring the acquired speech motor skills to a cognitively demanding situation. The results have clinical implications regarding optimal practice schedules for treatment intervention.